Variability in fruit physico-chemical characteristics of litchi (Litchi chinensis) in Tripura and Asom - SINGH, AWTAR; NATH, VISHAL (The Indian Journal of Agricultural Sciences, 2015)
Litchi (Litchi chinensis) improvement has been sought mainly through the selection of improved clones and very little work has been done in planned breeding programmes. The economic importance of litchi has led to the selection and breeding over thousands of years, which resulted in relatively few genotypes because of narrow genetic base and restricted germplasm variability. The present day need in litchi is to have cultivars with high fruit weight, high pulp content and small/chicken-tongued seeds coupled with prolonged shelf-life. Therefore, surveys to select the desirable clones of litchi were conducted in the litchi growing areas of Asom and Tripura during the fruiting season of 2007-08 to 2011-12. The superior clones differing in fruit maturity period, with heavy bearing were selected and characterized. The fruit characteristics were studied in the selected clones, which have exhibited a wide range of variation. Based on the characterization of various physico-chemical parameters in fruits, thirty-nine clones were identified. The important clones identified for different characteristics having (i) higher fruit weight A26 (22.29g/fruit), A1l (21.75g/fruit) and A15 (21.21g/fruit), (ii) high TSS (T9 (20.88°Brix), A23 (20.16°Brix) and T5 (19.88°Brix), (iii) small seeds (A26 (1.18g/seed), A25 (1.37g/seed) and A27 (1.95g/seed) and (iv) high pulp percentage/edible portion A26 (72.96%), T15 (69.83%) and T14 (68.63%) were identified. Two clones, viz. A10-1 and A25, having five or more of the desirable fruit quality attributes and fourteen clones having four desirable fruit quality characteristics were propagated vegetatively for detailed evaluation. It was concluded from the present study that there is ample scope for selection of the desirable clones from the existing variability in the litchi orchards of Tripura and Asom.